EVALUASI KINERJA MENGGUNAKAN METODE BALANCED SCORECARD PADA APOTEK XX YOGYAKARTA TAHUN 2019 - Muslim, Ahmad Suriyadi; Sunarni, Titik; Andayani, Tri Murti (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: The growth rate of pharmacy in the city of Yogyakarta is very rapid so that it can cause competition between pharmacy. Objective: Pharmacy service performance is very important to be reviewed because it can be used as a parameter to determine management strategies. One method that is recommended in assessing pharmacy performance is the balanced scorecard method. Methods: This research is non-experimental explorative descriptive design with the aim to find out the performance of the apotek XX Yogyakarta based on four perspectives of the balanced scorecard method, financial side, customer, internal business processes, learning and growth of pharmacy and provide recommendations for improvement based on the results of the performance evaluation. Data collection was conducted retrospectively and prospectively in the form of qualitative and quantitative data. Results: The results of the performance apotek XX Yogyakarta using the balanced scorecard method research from a financial perspective shows the value of ITOR has decreased every year, Internal business process perspective is still found the existence of DRP and pharmacies have not met 100% of drug needs and in the perspective of learning and employee productivity growth is valued less. Conclusion: However, over all the results are good because it meets the standard values.